Human primary skeletal muscle cells express glutamate receptor GluR3, are activated by glutamate, and are affected by autoimmune GluR3B antibodies of epilepsy patients - Levite, Mia; Ilouz, Nili; Harazi, Avi; Goldberg-Stern, Hadassa; Galun, Eithan; Mitrani-Rosenbaum, Stella (Frontiers in Physiology, 2025)
BackgroundGlutamate is the major excitatory neurotransmitter in the nervous system, common in neuromuscular junctions, and with abnormally reduced levels in several muscle diseases. Glutamate receptor AMPA GluR3, encoded by the GRIA3 gene, has important neurophysiological roles in regulation of neural networks, sleep, and breathing. GluR3 deletion or abnormal function increases the susceptibility to seizures and disrupts oscillatory networks of sleep, breathing, exploratory activity, and motor coordination.QuestionsDo human skeletal muscle cells express GluR3? Are they activated by glutamate? Do autoimmune GluR3B antibodies of Nodding Syndrome (NS) patients, and/or other intractable epilepsy patients, that bind and damage neural cells, also bind and affect skeletal muscle cells?ResultsWe discovered several original findings: 1) Human primary skeletal muscle cells (myoblasts) express GluR3 RNA and protein, evident by PCR and immunostaining, 2) glutamate (10−8–10−5M) increases intracellular sodium in human skeletal muscle cells and increases muscle cell number (probably by inducing muscle cell proliferation), 3) AMPA and NMDA increase intracellular sodium in skeletal muscle cells, 4) GluR3B monoclonal antibody binds skeletal muscle cells and increases their number, 5) autoimmune affinity-purified GluR3B antibodies of epileptic NS patients, suffering from nodding due to loss of muscle tone and muscle wasting, bind skeletal muscle cells, 6) purified IgGs rich in autoimmune GluR3B antibodies of intractable epilepsy patients bind and kill skeletal muscle cells.Possible implicationsTogether, the novel findings in this study may have various important implications on muscle physiology and pathology and call for continuation studies on diverse physiological, pathological and therapeutic topics. Meanwhile, we raise few hypotheses: 1) GluR3 has an important physiological role in muscle cells and motor function, 2) impaired GluR3 function (due to genetic/epigenetic/autoimmune/infectious/inflammatory factors?) can cause muscle impairments and motor problems, 3) glutamate, by direct activation of GluR3 and/or other GluRs expressed in skeletal muscle cells, can beneficially affect muscle cell survival, growth, and function, 3) Glutamate, iGluR agonists, and/or GluR3B mAb may have therapeutic effects for muscle diseases, injuries, and age-related sarcopenia, 4) autoimmune GluR3B antibodies of NS patients and/or other epilepsy patients may bind GluR3 in muscle cells, damage these cells, and induce muscle dysfunction and motor problems.